The genus Codonopsis (Campanulaceae): a review of phytochemistry, bioactivity and quality control - He, Jing-Yu (J Nat Med, 2014)
Codonopsis, in the family Campanulaceae, is a genus containing 42 species of dicotyledonous herbaceous perennial plants, predominantly found in Central, East and South Asia. Several Codonopsis species are widely used in traditional medicine and are considered to have multiple medicinal properties. Among the Codonopsis species, Codonopsis pilosula (Franch.) Nannf. and C. lanceolata (Sieb. et Zucc.) Benth. & Hook. f. ex Trautv. are more popular than others according to the findings, especially phytochemical and bioactive studies. Phytochemical research shows that Codonopsis species contain mainly polyacetylenes, phenylpropanoids, alkaloids, triterpenoids and polysaccharides, which contribute to multiple bioactivities. However, the mechanisms of their bioactivities need to be further elucidated. The less popular Codonopsis species remain to be studied and exploited. In addition, although a series of methods for the quality evaluation of Codonopsis species have been developed, a feasible and reliable approach to the efficacious and safe use of various Codonopsis species is still needed, with considering botanical origin, chemical constituents and bioactive effects. This review aims to provide up-to-date and comprehensive information on the phytochemistry, bioactivity and quality control of medicinal plants in the genus Codonopsis and to highlight current gaps in knowledge, which is useful for the wider development of the Codonopsis genus.